Bowen disease with matrical differentiation: Report of an exceptional histopathologic presentation. (29th June 2020) - Saggini, Andrea; Bang, Nicole; Hantschke, Markus; Held, Laura; Kempter, Wolfgang; Schärer, Leo
Abstract: Matrical differentiation is the distinctive feature of pilomatricoma and other purely matrical adnexal neoplasms; additionally, foci of matrical differentiation have been also described in hybrid cysts of Gardner syndrome, as well as in a wide variety of benign and malignant cutaneous tumors, including basal cell carcinoma. We report an exceptional case of Bowen disease exhibiting multiple foci of matrical differentiation, as confirmed by means of immunohistochemical studies. Several types of divergent, non‐squamous differentiation have been exceptionally reported in cutaneous squamous cell carcinoma in situ (cSCCIS), including sebaceous, mucinous/glandular, poroid, tricholemmal, and neuroendocrine differentiation; matrical differentiation may be added to this list. Our findings further emphasize the undifferentiated nature of neoplastic cells in cSCCIS.